2022
DOI: 10.1101/2022.03.30.486322
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neighbouring modifications interfere with the detection of phosphorylated alpha-synuclein at Serine 129: Revisiting the specificity of pS129 antibodies

Abstract: Alpha-synuclein (aSyn) within Lewy bodies, Lewy neurites, and other pathological hallmarks of Parkinson's disease and synucleinopathies have consistently been shown to accumulate in aggregated and phosphorylated forms of the protein, predominantly at Serine 129 (S129). Antibodies against phosphorylated S129 (pS129) have emerged as the primary tools to investigate, monitor, and quantify aSyn pathology in the brain and peripheral tissues. However, most of the antibodies and immunoassays aimed at detecting pS129-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 106 publications
(211 reference statements)
0
8
0
Order By: Relevance
“…We have recently shown that the aSyn pS129 antibody binding could be affected by the presence of aSyn PTMs neighbouring S129 (Lashuel et al, 2022), and hypothesised that sensitivity to neighbouring PTMs could also be applicable to other C-terminal as well as N-terminal or NAC region antibodies. Therefore, we investigated the reactivity of the non-modified aSyn antibodies in the presence of PTMs nearby their epitopes by DB and WB, and the results are summarised in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We have recently shown that the aSyn pS129 antibody binding could be affected by the presence of aSyn PTMs neighbouring S129 (Lashuel et al, 2022), and hypothesised that sensitivity to neighbouring PTMs could also be applicable to other C-terminal as well as N-terminal or NAC region antibodies. Therefore, we investigated the reactivity of the non-modified aSyn antibodies in the presence of PTMs nearby their epitopes by DB and WB, and the results are summarised in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…2F10-E12 110-115 and AB 134-138) of aSyn. Two additional antibodies were incorporated to cover the aSyn serine phosphorylations: AB EP1536Y pS129, as this antibody has been the most specific to aSyn pS129 species in our hands and in the literature (Delic et al, 2018; Lashuel et al, 2022), and LASH pS87, which was recently shown to detect LBs in PD and GCIs in MSA (Sonustun et al, 2022). For the N-terminal tyrosine phosphorylation modification, we opted for the monoclonal LASH-BL pY39 antibody.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The most likely reason for the selection of these antibody pairs is that the C-terminus of ␣SYN is the most immunogenic region and results in high affinity antibodies and thus better assay performance, as compared to N-terminal ␣SYN antibodies which exhibit in general a lower affinity thereby resulting in lower sensitivity assays. Nevertheless, it is possible that the multitude of C-terminal PTMs neighboring the epitopes of these antibodies could either eliminate or mask the epitope [42], or interfere with antibody binding to ␣SYN resulting in a biased analyte concentration. In addition, the great majority of ␣SYN immunoassays were developed based on the use of a single protein standard (full-length ␣SYN), which may have led to the downstream development of assays that do not necessarily capture the diversity of ␣SYN proteoforms.…”
Section: Introductionmentioning
confidence: 99%